PENGARUH REPUTASI INSTITUSI DAN KUALITAS PELAYANAN TERHADAP KEPUASAN MAHASISWA DI SEKOLAH TINGGI ILMU EKONOMI (STIE) AKA SEMARANG DENGAN KEPERCAYAAN SEBAGAI VARIABEL INTERVENING - Andre Aprilianto Suwardi; Bayu Kurniawan (Adbis: Jurnal Administrasi dan Bisnis, 2020)
The purpose of this study: to examine and analyze the effect of the institution's reputation, service quality on student satisfaction, with trust as an intervening variable. The study was conducted by accidental sampling technique, using the Slovin formula obtained a sample of 93 respondents. The data analysis technique used is the path analysis technique. The results of the study concluded that: Institutional reputation directly influences trust. Service quality has a direct effect on trust. Institutional reputation has a direct influence on student satisfaction. Service quality has a direct effect on student satisfaction. Trust has a direct influence on student satisfaction. Institutional reputation has an influence on student satisfaction through trust as an intervening variable. Service quality has an influence on student satisfaction through trust as an intervening variable. (3) human resources affect he quality of financial statements, (4) organizational commitment doesnt affect he quality of financial statements.